2016
DOI: 10.1002/adfm.201504857
|View full text |Cite
|
Sign up to set email alerts
|

Benchtop Fluorination of Fluorescent Nanodiamonds on a Preparative Scale: Toward Unusually Hydrophilic Bright Particles

Abstract: Fluorination of diamonds modulates their optical and electromagnetic properties and creates surfaces with increased hydrophobicity. In addition, fl uorination of diamonds and nanodiamonds has been recently shown to stabilize fl uorescent nitrogen-vacancy centers, which can serve as extremely sensitive single atomic defects in a vast range of sensing applications from quantum physics to high-resolution biological imaging. Traditionally, fl uorination of carbon nanomaterials has been achieved using harsh and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 91 publications
0
27
0
Order By: Relevance
“…1b). The NDs used are in average ∼33 nm in diameter with a fairly narrow size distribution41 (Supplementary Fig. 1) and coated with a HPMA shell a few nanometre thick, as indicated by transmission electron microscopy (TEM) image (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1b). The NDs used are in average ∼33 nm in diameter with a fairly narrow size distribution41 (Supplementary Fig. 1) and coated with a HPMA shell a few nanometre thick, as indicated by transmission electron microscopy (TEM) image (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that near‐surface NV centers strongly interact with the diamond surface and the functional groups present there . Fluorescence from these centers can be quenched, or their fluorescence properties at least significantly altered due to this interaction . NV centers separated less than about 10 nm are generally assumed to interact with the surface .…”
Section: Discussionmentioning
confidence: 99%
“…Although the spectral shapes and overall fluorescence of our FNDs were very similar to those of FNDs irradiated in an accelerator, we were interested in whether our procedure increases the homogeneity of irradiation, i.e., whether the material contains a higher fraction of FNDs. To distinguish the fluorescent and non-fluorescent NDs present in a large ensemble at the single-particle level 19 , 66 , we utilized simultaneous measurement of fluorescence-lifetime imaging microscopy (FLIM) and atomic force microscopy (AFM) (Supplementary Figure 7 ). We found that the fraction of FNDs in material irradiated in a nuclear reactor increased by a factor of 2.6 compared to optimally 41 p + -irradiated pellet target with NDs in an accelerator (49% vs. 19%).…”
Section: Resultsmentioning
confidence: 99%